The Secret History of the Soul Physiology, Magic and Spirit Forces from Homer to St Paul. - Sugg, Richard (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
What would Christianity be like without the soul? While most people would expect the Christian bible to reveal a highly traditional opposition of matter and spirit, the spirit forces of the Old and New Testaments are often surprisingly physical, dynamic, and practical, a matter of energy as much as ethics. The Secret History of the Soul examines the forgotten or suppressed models of body, soul, and human consciousness found in the literature, philosophy and scripture of the ancient and classi...
Table of contents; acknowledgements; abbreviations; introduction; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; conclusion; notes; index
Description based upon print version of record.
Keywords: Soul -- History of doctrines; Soul -- History; Soul -- Philosophy; Soul -- History of doctrines; Soul -- Philosophy; RELIGION / Christian Theology / Anthropology; Electronic books